Assessing Thyroid Disorder Awareness Among Pregnant Women: A Hospital-based Study in Kottayam - Anila C Eapen; Nisha George; Adilamol K.M.; Alphonsa Joy; Cicy George F.C.C.; Gopika P.G.; Manjusha S.; Swapna S.; Theresa Mathew S.Η. (International Journal of Community Health Nursing And Practices, 2025)
The current study was carried out at Caritas Hospital to evaluate the knowledge of pregnant women regarding thyroid disorders. The study aimed to assess the level of knowledge about thyroid disorders among pregnant women and to explore the relationship between knowledge levels and selected demographic factors. A total of 194 pregnant women attending the obstetrics and gynecology outpatient department at Caritas Hospital in Kottayam were included using a convenience sampling method. Structured questionnaires were utilized to assess their knowledge of thyroid disorders, and the data were analyzed using both descriptive and inferential statistical methods. The results indicated that among the 194 participants, 8.8% had poor knowledge, 86.6% had average knowledge, and 4.6% had good knowledge regarding thyroid disorders. The analysis revealed no significant association between the knowledge of pregnant women and demographic variables such as age, religion, occupation, family income, history of abortion, gravida status, and prior information. However, significant associations were found between knowledge levels and educational status, personal experiences with thyroid disorders, and a history of thyroid issues (p<0.05). The findings underscore important implications for nursing practice, education, administration, and future research. Nurses working in the Obstetrics & Gynecology department have a unique role in assessing the knowledge of pregnant women regarding thyroid disorders, and facilitating timely health education.
Keywords: Knowledge; Pregnant women; demographic factors; health education; thyroid disorders